Inequality, Crisis and Politics of outrage: The Reconfiguration of Post-Crisis Social Classes in the North Atlantic Region - Hayes, Matthew (2011)
By drawing on a Marxist perspective, the author ventures into an interpretation of the current economic crisis. The author suggest that the crisis is rooted in a long term process of radical transformation in the North Atlantic countries’s class relations. In particular, he maintains that the composition of classes existent in the 40s and 50s of the 20th century-relatively egalitarian, has changed due to broad transformations in the economies of the North Atlantic. The result has been the deterioration of those economies’s capacity to compete in the global economy, and increasing social inequality.